Recensión: Martín Ríos, Pilar: Digital forensics and criminal process in spain: evidence gathering in a changing context, Editorial Aranzadi, Cizur Menor (Navarra), 2022, 204 páginas, ISBN: 978-84-1125-277-5 - Pérez-Luño Robledo, Enrique César (IUS ET SCIENTIA, 2022)
Recensión de la obra: Martín Ríos, Pilar: Digital forensics and criminal process in spain: evidence gathering in a changing context, Editorial Aranzadi, Cizur Menor (Navarra), 2022, 204 páginas, ISBN: 978-84-1125-277-5